IMPLEMENTASI ANGGARAN BERBASIS KINERJA DAN AKUNTABILITAS SEKTOR PUBLIK Studi pada Pemerintah DIY - Enita Binawati (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2015)
The implementation of performance-based budget in Indonesia to materialize the accountability of a local government was influenced by various factors: Based on the survey of the study the objectives its objectives were: (1) to empirically examine the impact of leadership style, resources, information and goal orientation on the implementation of performance-based budget, (2) to empirically examine the impact of the implementation of the performance-based budget on financial and performance accountabilities, (3) to empirically examine the impact of the financial accountability on the performance accountability, and (4) to interpret and to empirically describe mimetic, coercive and normative isomorphism using institutional theory. The survey was conducted to 202 local government officers involved in budgetary preparation and decision making, consisting of five districts/city in the Special Region of Yogyakarta. The study used mixed method, which combined qualitative and quantitative approaches and sequential explanatory strategy. The hypotheses were tested using partial least square (PLS) analysis. The results of the survey showed that (1) the factors of the resources, the information and the goal orientation were proven to have significant impact on the implementation of the performance-based budget, (2) the implementation of the performance-based budget was proven to have significant impact on the financial and performance accountabilities, (3) the financial accountability was also proven to have significant impact on the performance accountability, and (4) there was normative and coercive institutional isomorphism in Satuan Kerja Perangkat Daerah (SKPD), working units of local government apparatus, of the Special Region of Yogyakarta. Keywords: the implementation of the performance-based budget, public sector accountability, institutional theory and mixed method.